Preventing Pruritus Vulvae and Maintaining Personal Hygiene at SMK Plus NU Sidoarjo - Diana, Wulan; Wilujeng, Sri; Rachman, Ziana Maulidiyah (Adi Husada Nursing Journal, 2023)
In Indonesia, 5, million young women often experience pruritus vulvae during menstruation, which is characterized by an itching sensation in the vagina. Poor personal hygiene is one of the factors that cause pruritus vulvae complaints. This study aims to determine the relationship between personal hygiene during menstruation and the incidence of pruritus vulvae in adolescents at SMK Plus NU Sidoarjo. The research design is analytic with a cross-sectional approach. The population of all teenagers in SMK plus Nu Sidoarjo with a sample size of 90 respondents was taken by proportional stratified sampling. The independent variable is personal hygiene and the dependent variable is pruritus vulvae. The research instrument is a questionnaire, analyzed by the Spearman rank test at a significance level of = 0,05. The results showed that half (50%) of adolescent girls had good personal hygiene and most (51,1%) had mild pruritus vulvae. Spearman rank test analysis obtained a value of P = 0,000, meaning that there is a relationship between personal and pruritus vulvae in adolescent girls at SMK Plus NU Sidoarjo. It can be concluded that the better personal hygiene, the lighter the incidence of pruritus vulvae, on the contrary, the less personal hygiene, the more severe the incidence of pruritus vulvae. It is expected that young women will carry out proper personal hygiene in order to maintain the health and cleanliness of the reproductive organs in preventing the occurrence of pruritus vulvae.